2019
DOI: 10.1016/j.ijheh.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxic effects of secondary metabolites of DEHP and its alternative plasticizers DINCH and DINP on a L929 cell line

Abstract: Background: Phthalic acid esters are widely used to improve the plasticity of PVC in medical devices (MD). The most famous plasticizer is DEHP, whose use in medical devices has been contested by the European authorities since 2008. Several alternative plasticizers are being considered to replace DEHP, such as DEHT, TOTM, DINP or DINCH, but they are also released from the PVC throughout their life cycle and are metabolized in the same way as DEHP. Objectives: Our study focuses on the in vitro cytotoxicity of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
(33 reference statements)
2
11
0
Order By: Relevance
“…19,20 Such observations are of public health importance, because first experimental evidence suggests the toxic potential of some of these alternatives, although their associations with toxicological consequences in general human populations are not well understood yet. 21,22 Children tend to exhibit higher intake amounts of phthalates than adults, because of their greater surface area to body weight ratio, 23 intake amount relative to body weight, 24 and likelihood of distinct behaviors (such as mouthing) that would increase exposure. 25 Phthalate exposures among children are, however, most extensively investigated for certain geographical regions such as North America, Europe, and East Asia.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19,20 Such observations are of public health importance, because first experimental evidence suggests the toxic potential of some of these alternatives, although their associations with toxicological consequences in general human populations are not well understood yet. 21,22 Children tend to exhibit higher intake amounts of phthalates than adults, because of their greater surface area to body weight ratio, 23 intake amount relative to body weight, 24 and likelihood of distinct behaviors (such as mouthing) that would increase exposure. 25 Phthalate exposures among children are, however, most extensively investigated for certain geographical regions such as North America, Europe, and East Asia.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several in vivo and in vitro toxicological studies have analyzed possible adverse effects of DINCH and contradictory results were obtained ( Campioli et al., 2015 ; Campioli et al., 2019 ; Campioli et al., 2017 ; David et al., 2015 ; EFSA, 2007 ; Eljezi et al., 2019 ; Engel et al., 2018 ; Nardelli et al., 2017 ; Vasconcelos et al., 2019 ). The in vivo toxicological studies of DINCH on rats have shown no effect on behavior, organ weight, serum chemistry ( David et al., 2015 ), and no evidence of reproductive toxicity or endocrine disruptive properties ( EFSA, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, DEHP has also been categorized as carcinogenic, mutagenic, or toxic for reproduction 1B under the Classification Labeling and Packaging (CLP) Regulation (Testai et al, 2016; Regulation (EU) 2017/745 [27]), due to suspected reprotoxicity in humans [10]. Moreover, DEHP-and especially its primary metabolite MEHP (mono(2-ethylhexyl)phthalate)-is also responsible for a significant decrease in cell viability as soon as reaching blood concentrations of 0.05 mg/mL and 0.01 mg/mL, respectively [28]. Our model (simulant) does not allow us to measure the exposure to MEHP, due to the absence of the esterase contained in the bloodstream (therefore, no metabolism can occur).…”
Section: Discussionmentioning
confidence: 99%